Re-evaluation of Diadenosine Tetraphosphate (Ap4A) From a Stress Metabolite to Bona Fide Secondary Messenger - Ferguson, Freya; McLennan, Alexander G.; Urbaniak, Michael D.; Jones, Nigel J.; Copeland, Nikki A. (Frontiers in Molecular Biosciences, 2020)
Cellular homeostasis requires adaption to environmental stress. In response to various environmental and genotoxic stresses, all cells produce dinucleoside polyphosphates (NpnNs), the best studied of which is diadenosine tetraphosphate (Ap4A). Despite intensive investigation, the precise biological roles of these molecules have remained elusive. However, recent studies have elucidated distinct and specific signaling mechanisms for these nucleotides in prokaryotes and eukaryotes. This review summarizes these key discoveries and describes the mechanisms of Ap4A and Ap4N synthesis, the mediators of the cellular responses to increased intracellular levels of these molecules and the hydrolytic mechanisms required to maintain low levels in the absence of stress. The intracellular responses to dinucleotide accumulation are evaluated in the context of the ‘friend’ and ‘foe’ scenarios. The ‘friend (or alarmone) hypothesis’ suggests that ApnN act as bona fide secondary messengers mediating responses to stress. In contrast, the ‘foe’ hypothesis proposes that ApnN and other NpnN are produced by non-canonical enzymatic synthesis as a result of physiological and environmental stress in critically damaged cells but do not actively regulate mitigating signaling pathways. In addition, we will discuss potential target proteins, and critically assess new evidence supporting roles for ApnN in the regulation of gene expression, immune responses, DNA replication and DNA repair. The recent advances in the field have generated great interest as they have for the first time revealed some of the molecular mechanisms that mediate cellular responses to ApnN. Finally, areas for future research are discussed with possible but unproven roles for intracellular ApnN to encourage further research into the signaling networks that are regulated by these nucleotides.